Answer:
No
Step-by-step explanation:
5(-3)= -15
5(1)= 5
-15+5=-10
-10 is greater than -19 not less than or equal too.
Hope this helps!
Answer:
n = 1 second formula
n = 0 first formula
Step-by-step explanation:
I answer this in the other question you put, here it is again.
This is easy to get. We know the sequence cause it follows a pattern of 8, so let's try some values of n from 1 to 4, to get those numbers with the first formula:
n = 1,2,3,4
f(1) = 8(1) + 2 = 10
f(2) = 8(2) + 2 = 18
f(3) = 8(3) + 2 = 26
f(4) = 8(4) + 2 = 34
As you can see, with the first formula, the first term is 10, and not 2. The only way to get 2 with n = 1 is with the second formula:
f(1) = 8(1) - 6 = 2
f(2) = 8(2) - 6 = 10
f(3) = 8(3) - 6 = 18
f(4) = 8(4) - 6 = 26
With n = 1, the second formula was better and correct.
The first formula could be right only beggining with n = 0. Here is the proof:
f(0) = 8(0) + 2 = 2
Answer:
10.5
Step-by-step explanation:
2⅝×4=10.5
..............
Answer:
indeed it does
Step-by-step explanation:
wheres the diagram exactly?
Answer:
B,AD
Step-by-step explanation:
BECAUSE I SAY IT